Cross‐talk between monocyte invasion and astrocyte proliferation regulates scarring in brain injury. (9th April 2018) - Frik, Jesica; Merl‐Pham, Juliane; Plesnila, Nikolaus; Mattugini, Nicola; Kjell, Jacob; Kraska, Jonas; Gómez, Ricardo M; Hauck, Stefanie M; Sirko, Swetlana; Götz, Magdalena
Abstract: Scar formation after brain injury is still poorly understood. To further elucidate such processes, here, we examine the interplay between astrocyte proliferation taking place predominantly at the vascular interface and monocyte invasion. Using genetic mouse models that decrease or increase reactive astrocyte proliferation, we demonstrate inverse effects on monocyte numbers in the injury site. Conversely, reducing monocyte invasion using CCR2 −/− mice causes a strong increase in astrocyte proliferation, demonstrating an intriguing negative cross‐regulation between these cell types at the vascular interface. CCR2 −/− mice show reduced scar formation with less extracellular matrix deposition, smaller lesion site and increased neuronal coverage. Surprisingly, the GFAP + scar area in these mice is also significantly decreased despite increased astrocyte proliferation. Proteomic analysis at the peak of increased astrocyte proliferation reveals a decrease in extracellular matrix synthesizing enzymes in the injury sites of CCR2 −/− mice, highlighting how early key aspects of scar formation are initiated. Taken together, we provide novel insights into the cross‐regulation of juxtavascular proliferating astrocytes and invading monocytes as a crucial mechanism of scar formation upon brain injury. Synopsis: Astrocytes resume proliferation specifically at the vascular wall after brain injury. Genetic increase of astrocyte proliferation reduces monocyte invasion at the injury site, while lack of monocyte invasion promotes astrocyte proliferation and reduces the GFAP + scar. Reactive astrocytes proliferate at blood vessels after brain injury and show nuclear localisation of the aryl hydrocarbon receptor. Increased juxtavascular astrocyte proliferation decreases monocyte invasion at the injury site. Block of monocyte invasion in CCR2 −/− mice leads to increased juxtavascular astrocyte proliferation and reduced scar formation. Abstract : Astrocytes resume proliferation specifically at the vascular wall after brain injury. Genetic increase of astrocyte proliferation reduces monocyte invasion at the injury site, while lack of monocyte invasion promotes astrocyte proliferation and reduces the GFAP + scar.